2019
DOI: 10.3390/ijerph16224385
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a Pedometer-Based, 24-Week Walking Intervention on Depression and Acculturative Stress among Migrant Women Workers

Abstract: Little research has examined exercise-based interventions meant to alleviate depressive symptoms among Korean-Chinese migrant women workers living in Korea. Thus, this study evaluated the effectiveness of a 24-week walking program on reducing depressive symptoms and acculturative stress levels in this population. This quasi-experimental sequential walking program was conducted with 132 Korean-Chinese women over a period of 24 weeks. Participants were divided into either a standard treatment group (n = 69) or e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(34 citation statements)
references
References 36 publications
0
34
0
Order By: Relevance
“…Findings of our review also indicated the benefits of using smartphone-based technology for the purposes of motivation and assistance [ 40 , 42 , 43 , 44 , 45 ]. Our findings are in accordance with other studies using phone text-message psychosocial intervention therapies, which found significant improvements in mood and depression among vulnerable groups of immigrant women, challenging previous notions that phone-based navigation for immigrants is difficult [ 62 , 63 ].…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations
“…Findings of our review also indicated the benefits of using smartphone-based technology for the purposes of motivation and assistance [ 40 , 42 , 43 , 44 , 45 ]. Our findings are in accordance with other studies using phone text-message psychosocial intervention therapies, which found significant improvements in mood and depression among vulnerable groups of immigrant women, challenging previous notions that phone-based navigation for immigrants is difficult [ 62 , 63 ].…”
Section: Discussionmentioning
confidence: 88%
“…Five (23%, 5/22) studies utilized mobile-based technologies for various purposes including intervention administration, and motivational or assistive reminders [ 40 , 42 , 43 , 44 , 45 ]. The administration of a walking intervention among Korean–Chinese midlife women found that the use of a mobile-phone-based pedometer was practical for accurately self-monitoring daily physical activity [ 44 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…With the development of living standards, more research has started to focus on the impact of walking on individuals’ mental health. In past studies, there is abundant evidence that walking promotes recovery from mental health disorders [ 21 , 22 ] and is an important measure to improve mental health [ 23 , 24 ]. Kekäläinen et al [ 25 ] demonstrated that walking was positively associated with participants’ mental, social, and subjective health.…”
Section: Introductionmentioning
confidence: 99%